Quantification of changeability level for engineering systems. Issue 1 (19th September 2018) - Rehn, Carl F.; Pettersen, Sigurd S.; Garcia, Jose J.; Brett, Per O.; Erikstad, Stein O.; Asbjørnslett, Bjørn E.; Ross, Adam M.; Rhodes, Donna H.
Abstract: This paper outlines a generic method for quantifying changeability level, to support better decision making in the early stages of design of engineering systems. Changeability represents the ability of a system to change form, function, or operation, and is a collective term for characteristics such as flexibility, adaptability, and agility. Quantification of changeability level must not be confused with valuation of changeability. The level of changeability in a design is essentially under the control of the designer. Two aspects of changeability are discussed, the first being how to structure changeable design alternatives using the Design for Changeability (DFC) variable. The DFC variable represents combinations of path enablers built into a design. Path enablers are characteristics of systems enabling them to change more easily. The second aspect is to quantify the level of changeability for a given design alternative, based on change cost and time. For the latter, we propose two measures for quantification: (1) bottom‐up, measuring the reduction of cost and time enabled for each relevant change, and (2) top‐down, measuring the span of change opportunities at given cost and time thresholds. A case study of a ship is presented to demonstrate the proposed generic method.